1H NMR-based metabolomics analyses in children with Helicobacter pylori infection and the alteration of serum metabolites after treatment. (October 2020) - Fang, Ling-Juan; Lin, Xiao-Chun; Huang, Dian; Pan, Tong-Tong; Yan, Xiu-Mei; Hu, Wei-Guo; Zhu, Huan; Xu, Zhang; Zhu, Xiao-Zhou; Lu, Hua-Jun; Chen, Gui-Ping; Huang, Kai-Yu
Abstract: Background and aims: Helicobacter pylori ( H. p ylori) infection can occur in early childhood, without eradication therapies such infection can persist throughout life and cause many different diseases. This study investigated the metabolic characteristics and explored the underlying mechanism of children with H. pylori infection, and identified potential biomarkers for evaluating the efficacy of H. pylori eradication therapies. Methods: We performed 1 H NMR-based metabonomics coupled with multivariate analysis to investigate the metabolic profiling of serum samples between Children with and without H. pylori infection. In the same manner, we compared the alternations of metabolites in H. pylori -infected children before and after H. pylori eradication therapies. Results: 21 metabolites from serum in H. pylori -infected and H. pylori -uninfected children were identified, which were mainly involved in energy, amino acid, lipid and microbial metabolism. We found that the serum levels of trimethylamine N -oxide and alanine were significantly higher in H. pylori- infected children compared to uninfected sera, whereas lactate was significantly lower. We also found that the levels of trimethylamine N -oxide and creatine in H. pylori -infected children was significantly decreased after H. pylori eradication therapies, whereas lactate and low-density lipoprotein/very low-density lipoprotein was significantly increased. Conclusions: This is the first study using 1 H NMR-based metabolomics approach to explore the effects of H. pylori infection in children. Our results demonstrated that the disturbances of metabolism in energy, amino acids, lipids and microbiota could play an important role in the pathogenesis of gastrointestinal and extragastric diseases caused by H. pylori infection. Trimethylamine N -oxide and lactate might serve as potential serum biomarkers for evaluating the efficacy of H. pylori eradication therapies. Highlights: This is the first study using 1 H NMR-based metabolomics approach to explore the effects of H. pylori infection in children. Various metabolite alterations might play an important role in the pathogenesis of H. pylori infection in children. The disturbances in metabolism could be recovered in H. pylori -infected children after eradication therapies. TMAO and lactate might be useful as biomarkers for evaluating the success of H. pylori eradication therapies.